A.M./A.M. para Memória Futura: Dois Homens que Lutaram Contra a Ditadura dos Dois Lados da Fronteira e Meios de Produção de Memória - Baía, João (Trabalhos de Antropologia e Etnologia, 2020)
In Bragança city there is a neighborhood, a school, a street, and a garden named Artur Mirandela. A monument was also erected in his honor in the same city. Despite the existence of these memorials there is no specific published research about this personality. During the Spanish Civil War, he has helped the Galician and POUMist refugee Alberto Mezquita to cross the country to Lisbon to try to embark for Latin America. Some hypotheses will be pointed and discussed in this article for Artur Mirandela not to be inscribed in the local, national and international history.